2021
DOI: 10.1371/journal.pone.0255596
|View full text |Cite
|
Sign up to set email alerts
|

Parent reports of children’s emotional and behavioral problems in a low- and middle- income country (LMIC): An epidemiological study of Nepali schoolchildren

Abstract: Background As epidemiological data on child mental health in low- and middle-income countries are limited, a large-scale survey was undertaken to estimate the prevalence and amount of child emotional and behavioral problems (EBP) in Nepal as reported by the parents. Methods 3820 schoolchildren aged 6–18 years were selected from 16 districts of the three geographical regions of Nepal, including rural, semi-urban and urban areas. We used the Nepali version of the Child Behavior Checklist (CBCL)/6-18 years as s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 44 publications
3
15
2
Order By: Relevance
“…Compared to similar national surveys that used screening tools, the general prevalence in our study remains higher [ 25 27 ]. Specifically, the percentage of Nepali children who scored in the clinical range on the child behavior checklist (CBCL) was 19% in a national survey [ 28 ], while in Germany, 14.5% of children and adolescents screened positive for psychiatric disorders in the national mental health and examination survey [ 27 ]. In a 2-stage epidemiological study using the SDQ in Saudi Arabia, however, the prevalence of any psychiatric disorder was 36% [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Compared to similar national surveys that used screening tools, the general prevalence in our study remains higher [ 25 27 ]. Specifically, the percentage of Nepali children who scored in the clinical range on the child behavior checklist (CBCL) was 19% in a national survey [ 28 ], while in Germany, 14.5% of children and adolescents screened positive for psychiatric disorders in the national mental health and examination survey [ 27 ]. In a 2-stage epidemiological study using the SDQ in Saudi Arabia, however, the prevalence of any psychiatric disorder was 36% [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…To assess the internal consistency of the Nepali version of CBCL/6-18 for the present study, we computed Cronbach’s alphas for the empirically based syndrome scales. The results are reported in a previous paper [ 4 ] and were: Withdrawn / Depressed: 0.71; Somatic Complaints: 0.79; Anxious / Depressed: 0.76; Rule-breaking Behavior: 0.76; Aggressive Behavior: 0.88; Social Problems: 0.73; Attention Problems: 0.80; Thought Problems: 0.75 [ 4 ].…”
Section: Methodsmentioning
confidence: 68%
“…This result contrasts with other studies where children of the lowest educated parents had more EBP [ 11 13 ]. One explanation may be the inclusion of illiterate parents from indigenous groups/ ethnic minorities in our sample [ 4 ]. International studies have reported that parents of ethnic minorities maybe less likely to perceive EBP in their children as compared to parents of ethnic majority groups due to less acknowledgement of such problems [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations